Business Plan of THE HIVE Cafeteria & Coworking Space in Vietnam - Thai, Vuong Hoang Chau (2025)
The Hive Cafeteria & Coworking Space is a business model that offers food and beverages for self-service pick-up at the counter, creating two separate spaces. The proposed project is aimed at students, office workers, and freelancers. This research is determined to fill the gap of a lack of flexible working space along with the application of new technology in the F&B market, which current competitors have not met the needs of customers. The thesis applies analytical methods and uses strategic tools such as SWOT and PEST analysis, Porter's Five Forces to assess the levels of competition or environmental factors and outlines market segments, marketing mix, operational plan and presents detailed financial plans as well as illustrates potential profitability. Combining business theory and practical application, the business plan aims to evaluate The Hive's feasibility and growth potential to expand to multiple branches nationwide.